2015
DOI: 10.1021/acs.cgd.5b00695
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystalline Phase Induced by Molecular Rotator and Dipole Fluctuation

Abstract: The thermal properties, crystal structures, dielectric relaxations, and rotational potential energy curves were examined for new rod-like molecules 1 and 2 bearing three aromatic rings connected by two -CONH-linkage groups to clarify the dynamic molecular behavior and phase transition behavior of the molecular assemblies. The molecular structures of 1 and 2 differed in that the central aromatic ring was phenyl (-C 6 H 4 -) in 1 and pyridyl (-C 5 NH 3 -) in 2, which affected the phase transition behavior owing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…It was found, however, that 2° amides could form liquid crystal phases, although these materials showed high melting points which were attributed to the presence of strong hydrogen bonding. 3 Careful molecular design using a selection of suitable lateral substituents and terminal groups attached to the mesogenic units allowed the melting point to be manipulated and a range of calamitic [4][5][6][7][8][9][10][11][12][13] and bent-core [14][15][16][17][18] liquid crystalline materials based around secondary amide groups have been reported. These systems tend to predominantly form smectic phases, again attributed to intermolecular hydrogen bonding between the amide groups.…”
Section: Page 1 Of 31mentioning
confidence: 99%
“…It was found, however, that 2° amides could form liquid crystal phases, although these materials showed high melting points which were attributed to the presence of strong hydrogen bonding. 3 Careful molecular design using a selection of suitable lateral substituents and terminal groups attached to the mesogenic units allowed the melting point to be manipulated and a range of calamitic [4][5][6][7][8][9][10][11][12][13] and bent-core [14][15][16][17][18] liquid crystalline materials based around secondary amide groups have been reported. These systems tend to predominantly form smectic phases, again attributed to intermolecular hydrogen bonding between the amide groups.…”
Section: Page 1 Of 31mentioning
confidence: 99%
“…The thermal stability and phase transition behaviors of Cn-BSNDIs are dominated by the intermolecular interactions and the conformational freedom of the alkyl chains. In general, the existence of flexible long alkyl chains enhances the conformational freedom in molecular assembly, which was the origin of the complicated phase transition behavior. In the molecular assembly of Cn-BSNDI , the electrostatic cation–anion Coulomb interaction is the most dominant one, while the multiple van der Waals interaction between alkyl chains impacts on the thermal stability of the molecular assembly and the packing structure. In particular, long alkyl chains tend to assemble to form a lamellar-type 2D molecular assembly. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Variations in the energy scale of intermolecular interactions have been utilized in the construction of functional π-molecular assemblies, where electrostatic (∼100 kJ mol –1 ), charge-transfer (10–20 kJ mol –1 ), hydrogen-bonding (5–20 kJ mol –1 ), and van der Waals (∼2 kJ mol –1 ) interactions are commonly observed. Simultaneous operation of multiple intermolecular interactions can form a closest-packing molecular assembly structure, where the coexistence of different energy-scale intermolecular interactions plays an important role in the phase transition behavior and crystal polymorphs. A characteristic intermolecular interaction has been utilized for constructing functional molecular assemblies. For instance, directional hydrogen-bonding interactions form one-dimensional (1D), two-dimensional (2D), and three-dimensional (3D) molecular assembly structures, while the charge-transfer interaction between the electron donor and acceptor generates the carriers in electrically conductive crystals. , Among these intermolecular interactions, weak van der Waals interactions between alkyl chains play an important role in the fabrication of hydrophobic molecular assembly structures utilizing multiple intermolecular interactions. , Such crystal engineering point of view is essential to design functional molecular assembly structures, where physical properties have been dominated by the magnitude and dimensionality of the intermolecular interactions. , …”
Section: Introductionmentioning
confidence: 99%
“…Because the LC states of 1 and 2 were governed by weak intermolecular interactions, the introduction of a strong intermolecular interaction such as hydrogen bonding should induce a different assembly structure. Because compound 4 could form intermolecular hydrogen bonds along the short axis of the molecule between dihydropyrazine and carbonyl units, 20 we anticipated that this compound could form a thermodynamically stable higher-ordered LC phase. The TG analysis of 4 revealed that it possessed high thermal stability up to 573 K (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%